Development of a risk stratification and prevention index for stratified care in chronic low back pain. Focus: yellow flags (MiSpEx network). (November 2017) - Wippert, Pia-Maria; Puschmann, Anne-Katrin; Drießlein, David; Arampatzis, Adamantios; Banzer, Winfried; Beck, Heidrun; Schiltenwolf, Marcus; Schmidt, Hendrik; Schneider, Christian; Mayer, Frank
Abstract: Introduction: Chronic low back pain (LBP) is a major cause of disability; early diagnosis and stratification of care remain challenges. Objectives: This article describes the development of a screening tool for the 1-year prognosis of patients with high chronic LBP risk (risk stratification index) and for treatment allocation according to treatment-modifiable yellow flag indicators (risk prevention indices, RPI-S). Methods: Screening tools were derived from a multicentre longitudinal study (n = 1071, age >18, intermittent LBP). The greatest prognostic predictors of 4 flag domains ("pain, " "distress, " "social-environment, " "medical care-environment") were determined using least absolute shrinkage and selection operator regression analysis. Internal validity and prognosis error were evaluated after 1-year follow-up. Receiver operating characteristic curves for discrimination (area under the curve) and cutoff values were determined. Results: The risk stratification index identified persons with increased risk of chronic LBP and accurately estimated expected pain intensity and disability on the Pain Grade Questionnaire (0–100 points) up to 1 year later with an average prognosis error of 15 points. In addition, 3-risk classes were discerned with an accuracy of area under the curve = 0.74 (95% confidence interval 0.63–0.85). The RPI-S also distinguished persons with potentially modifiable prognostic indicators from 4 flag domains and stratified allocation to biopsychosocial treatments accordingly. Conclusion: The screening tools, developed in compliance with the PROGRESS and TRIPOD statements, revealed good validation and prognostic strength. These tools improve on existing screening tools because of their utility for secondary preventions, incorporation of exercise effect modifiers, exact pain estimations, and personalized allocation to multimodal treatments. Abstract : Supplemental Digital Content is Available in the Text.Two new screening tools identify increased risk of chronic low back pain and potentially treatment-modifiable prognostic indicators in 4 yellow flag domains.